Transcriptomic and Lipidomic Mapping of Macrophages in the Hub of Chronic Beta-Adrenergic-Stimulation Unravels Hypertrophy-, Proliferation-, and Lipid Metabolism-Related Genes as Novel Potential Markers of Early Hypertrophy or Heart Failure - Sophie Nadaud; Mathilde Flamant; Wilfried Le Goff; Elise Balse; Catherine Pavoine (Biomedicines, 2022)
Sympathetic nervous system overdrive with chronic release of catecholamines is the most important neurohormonal mechanism activated to maintain cardiac output in response to heart stress. Beta-adrenergic signaling behaves first as a compensatory pathway improving cardiac contractility and maladaptive remodeling but becomes dysfunctional leading to pathological hypertrophy and heart failure (HF). Cardiac remodeling is a complex inflammatory syndrome where macrophages play a determinant role. This study aimed at characterizing the temporal transcriptomic evolution of cardiac macrophages in mice subjected to beta-adrenergic-stimulation using RNA sequencing. Owing to a comprehensive bibliographic analysis and complementary lipidomic experiments, this study deciphers typical gene profiles in early compensated hypertrophy (ECH) versus late dilated remodeling related to HF. We uncover cardiac hypertrophy- and proliferation-related transcription programs typical of ECH or HF macrophages and identify lipid metabolism-associated and Na+ or K+ channel-related genes as markers of ECH and HF macrophages, respectively. In addition, our results substantiate the key time-dependent role of inflammatory, metabolic, and functional gene regulation in macrophages during beta-adrenergic dependent remodeling. This study provides important and novel knowledge to better understand the prevalent key role of resident macrophages in response to chronically activated beta-adrenergic signaling, an effective diagnostic and therapeutic target in failing hearts.